Changing Patterns of Resilience: Exploring the Local. (2nd July 2020) - Bacon, Nicola; Goodship, Paul
Abstract: The notion of resilience is often referred to in relation to data services or the effects of climate change. However, understanding of social resilience and how it can vary across urban districts over time is vital too. Social Life co‐founder Nicola Bacon and data scientist Paul Goodship outline the research organisation's resilience mapping with the London Borough of Hounslow, which supported a better understanding of community dynamics and decision‐making.